2009
DOI: 10.1111/j.1469-7610.2008.02039.x
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial development from childhood to adolescence: a multi‐informant perspective with Canadian and Italian longitudinal studies

Abstract: The present studies investigated levels of prosocial behaviours from childhood to adolescence, using a multi-informant, cross-cultural perspective. All but one of the developmental trajectories identified were characterised by stable or declining levels of prosocial behaviours. Further research longitudinally investigating prosociality across developmental periods is needed to clarify prosocial behaviour development over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
98
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 34 publications
19
98
0
4
Order By: Relevance
“…That being said, most of the research done on prosocial behavior has examined helping behaviors enacted toward strangers (Einolf 2010;Eisenberg et al 2006;Staub 1995), although most people are more likely to help those who are relatively important in their lives, such as family members and friends Montemayor 1998, 1999;Killen and Turiel 1998;van der Mark et al 2002;Young et al 1999). Indeed, Natel-Vivier et al (2009) postulated that, as they get older, adolescents' prosocial responding becomes more selective and focused in nature, even rendering helping behaviors more ''private'' over time as teens become more involved with affiliated groups (e.g. family, friends).…”
Section: Prosocial Behaviormentioning
confidence: 98%
“…That being said, most of the research done on prosocial behavior has examined helping behaviors enacted toward strangers (Einolf 2010;Eisenberg et al 2006;Staub 1995), although most people are more likely to help those who are relatively important in their lives, such as family members and friends Montemayor 1998, 1999;Killen and Turiel 1998;van der Mark et al 2002;Young et al 1999). Indeed, Natel-Vivier et al (2009) postulated that, as they get older, adolescents' prosocial responding becomes more selective and focused in nature, even rendering helping behaviors more ''private'' over time as teens become more involved with affiliated groups (e.g. family, friends).…”
Section: Prosocial Behaviormentioning
confidence: 98%
“…The authors were surprised that the boys were found to decline or, at best, stay stable in prosocial behaviors into adolescence. Nantel-Vivier et al (2009) extended the age of observation with a cross-national comparison of 1,037 boys from 10 to 15, with mother and teacher reports of prosocial behaviors for a Canadian sample and teacher and student reports for an Italian sample. Although differences existed between samples and by who reported (students, mothers, or teacher), similar declines in trajectories were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it appears that children, like Machiavelli's Prince, learn how to identify the specific circumstances in which they need not be prosocial (Hay, 1994), restricting prosocial behaviors to their affiliate groups (i.e. their in-groups), which include their friends and family during this period of adolescence (Nantel-Vivier et al, 2009).…”
Section: What Are Prosocial Behaviors and How Do They Develop?mentioning
confidence: 99%
“…Examples include helping, sharing, cooperation (Nantel-Vivier et al, 2009), sympathy, and comforting (Scourfield, John, Martin, & McGuffin, 2004). Prosocial behaviors that facilitate positive social relations are thought to decline during early adolescence (Scourfield et al, 2004), when children learn how to maintain a balance between their selfinterests and their prosocial impulses (Hay, 1994), and then increase again with the maturation of empathic concern during late adolescence (Clark & Giacomantonio, 2013;Eisenberg & Fabes, 1998;Nantel-Vivier et al, 2009). Therefore, it appears that children, like Machiavelli's Prince, learn how to identify the specific circumstances in which they need not be prosocial (Hay, 1994), restricting prosocial behaviors to their affiliate groups (i.e.…”
Section: What Are Prosocial Behaviors and How Do They Develop?mentioning
confidence: 99%